European dishes going wild - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Game farm operators in South Africa are developing ways to boost game-meat exports to Europe. According to Theuns Eloff, head of Potchefstroom University Centre for Wildlife Economics, European Union inspectors have already given a green light for...